L’enseignement de la mécanique quantique grâce à un récit de fiction - Fabrice Ferlin; Philippe Lautesse; Juliette Tuaillon; Jean-Loup Héraud; Lionel Chaussard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In higher education in France, in the third year of the physics degree course, the teaching of quantum mechanics is essentially quantitative and formalism is presented as part of the standard interpretation. Moreover, some universities also offer an introduction to quantum mechanics in the second year, including both conceptual and computational teaching. In this article we propose to introduce an epistemological investigation of the physical concepts operating within quantum mechanics, at second-year level, by taking an interest in the delicate so-called measurement problem. We hypothesize that lecturers could approach this investigation via a realistic fiction narrative, G. Egan’s novel Quarantine. We draw on a theoretical framework, derived from Lewis' work, to show the relevance of this novel for use in a second-year quantum mechanics course.